The hedge fund compliance and risk management guide - Guizot, Armelle (John Wiley & Sons, 2007)
The Hedge Fund Compliance and Risk Management Guide provides you with a broad examination of the most important compliance and risk management issues associated with today’s hedge funds. Straightforward and accessible, this invaluable resource covers everything from how hedge funds continue to generate lucrative returns to why some use sophisticated instruments and financial engineering to get around fundamental regulatory laws.